The Social Basis of the Rational Citizen: How Political Communication in Social Networks Improves Civic Competence - Richey, Sean (Lexington Books, 2013)
Social networking fascinates scholars, pundits, and a billion Facebook users; this book shows that whom we know has a vast impact on our political beliefs, actions, and abilities. Prior scholarship has shown that networks are crucial to explaining everything from how bills get through Congress, why people vote, how NGO’s become successful in developing nations, and much more. Yet an in-depth analysis of the social basis of the rationality is missing. To fill this void, The Social Basis of the Rational Citizen provides the first empirical analysis of the most important hypothesized effect of social network influence on politics: social cognition. Through new lab experiments and survey data, this book shows that decision-making in groups promotes more rational choices and better citizenship. Thus, advice and learning derived from social network contacts are shown to be the basis of decision-making for the rational citizen.